The Role of Brand Image in Consumer Decision-Making: Evidence from The Body Shop Indonesia - Mohamad Rizaldi, Fikri; Suprayogi, Yogi (Fakultas Pendidikan Ekonomi dan Bisnis, 2024)
Purpose—This study examines the influence of brand image on consumer purchasing decisions for The Body Shop Body Mist products in Bandung, Indonesia. As competition in the cosmetics industry intensifies, companies must establish a strong brand image to differentiate themselves and maintain consumer loyalty. This research seeks to determine how consumers perceive The Body Shop's brand image, the key factors influencing purchasing decisions, and the extent to which brand image affects consumer behavior.Design/methods/approach – This study employs a quantitative research approach with a descriptive and causal research design. The sample consists of Body Mist consumers from The Body Shop Bandung, selected using non-probability purposive sampling. Data were collected through structured questionnaires and analyzed using simple linear regression and t-test analysis in SPSS. The analysis measures the statistical significance of the relationship between brand image and purchasing decisions, following the positivist paradigm.Findings– The results confirm that brand image significantly influences purchasing decisions, with a t-value of 42.583 exceeding the t-table value of 1.660 at a 0.000 significance level. A one-unit increase in brand image raises purchase decisions by 0.344 units. Consumers in Bandung perceive The Body Shop as a high-quality, ethical, and eco-friendly brand, enhancing trust and purchase intent, consistent with studies on brand equity and consumer behavior.Research implications/limitations—This study offers insights into how brand image shapes consumer purchasing decisions in the cosmetics industry. Strengthening sustainability branding, ethical business practices, and digital marketing can enhance brand perception and engagement. However, findings are limited to The Body Shop’s Body Mist category in Bandung, reducing generalizability. Future research should compare competing brands, digital branding strategies, and customer loyalty programs.Originality/value–This research expands knowledge on brand image and consumer behavior in Indonesia’s ethical beauty market. By focusing on The Body Shop’s sustainability-driven branding, it provides empirical evidence on brand perception in emerging markets. The findings benefit academics, marketers, and business strategists aiming to refine brand positioning and competitive advantage in the cosmetics industry